2022
DOI: 10.26508/lsa.202201362
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 endosomes and Pericentrin coordinate centrosome movement during pre-abscission in vivo

Abstract: The last stage of cell division involves two daughter cells remaining interconnected by a cytokinetic bridge that is cleaved during abscission. Conserved between the zebrafish embryo and human cells, we found that the oldest centrosome moves in a Rab11-dependent manner towards the cytokinetic bridge sometimes followed by the youngest. Rab11-endosomes are organized in a Rab11-GTP dependent manner at the mother centriole during pre-abscission, with Rab11 endosomes at the oldest centrosome being more mobile compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Here we tested the requirement of Rab11, Rab8, and Rab35 on KV lumen establishment using two strategies, morpholino (MO) transcript depletion using MOs that have been previously characterized ((Omori et al ., 2008; Westlake et al ., 2011; Kuhns et al ., 2019), Figure S3A) and an acute optogenetic clustering strategy (Figure 3A). The optogenetic strategy causes an acute inhibition of Rab11-, Rab8-, and Rab35-associated membranes through a hetero-interaction between cyptochrome2 (CRY2) and CIB1 upon exposure to blue light during specific KV developmental stages (Figure 3A, (Nguyen et al ., 2016; Rathbun et al ., 2020b; Krishnan et al ., 2022)). With acute optogenetic clustering of Rab11- and Rab35-associated membranes and with depletion of Rab11 and Rab35 transcripts using MOs, we found severe defects in lumen formation (Figure 3B-D, S3B-F) when comparing to control conditions (CRY2, Figure S3C; control MO, S3D-E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we tested the requirement of Rab11, Rab8, and Rab35 on KV lumen establishment using two strategies, morpholino (MO) transcript depletion using MOs that have been previously characterized ((Omori et al ., 2008; Westlake et al ., 2011; Kuhns et al ., 2019), Figure S3A) and an acute optogenetic clustering strategy (Figure 3A). The optogenetic strategy causes an acute inhibition of Rab11-, Rab8-, and Rab35-associated membranes through a hetero-interaction between cyptochrome2 (CRY2) and CIB1 upon exposure to blue light during specific KV developmental stages (Figure 3A, (Nguyen et al ., 2016; Rathbun et al ., 2020b; Krishnan et al ., 2022)). With acute optogenetic clustering of Rab11- and Rab35-associated membranes and with depletion of Rab11 and Rab35 transcripts using MOs, we found severe defects in lumen formation (Figure 3B-D, S3B-F) when comparing to control conditions (CRY2, Figure S3C; control MO, S3D-E).…”
Section: Resultsmentioning
confidence: 99%
“…Since Rab11, Rab8, and Rab35 are broadly expressed during zebrafish embryo development [22,[25][26][27], we chose to employ an optogenetic strategy to acutely inhibit their function during KV development. This optogenetic strategy causes an acute inhibition of CIB1-Rab11-, CIB1-Rab8-, and CIB1-Rab35-associated membranes through a hetero-interaction between cyptochrome2 (CRY2) and CIB1 upon exposure to blue light during KV developmental stages [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Rab11 endosomes are crucial for ciliary biogenesis (Knödler et al, 2010), interact with mother centriole appendages in interphase cells (Hehnly et al, 2012), traffic spindle assembly proteins to centrosomes and spindle for proper spindle alignment and cytokinesis (Hehnly and Doxsey, 2014, Hehnly et al, 2012). Illustrating their key role in cell division, Rab11 endosomes are involved in centrosome movement towards the cytokinetic bridge and necessary for cell abscission (Krishnan et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In human cells, centrosomes have been observed to be motile at the end of mitosis, when the centrosomes reorient themselves towards the midbody ( Piel et al, 2001 ). Interestingly, recent work has demonstrated that this centrosome motility involves the Rab11-dependent localization of PCNT to the centrosomes ( Krishnan et al, 2022 ). It is not known whether Kinesin-1 is involved in midbody-directed movement, but Kinesin does localize to centrosomes ( Neighbors et al, 1988 ) and interacts with PCNT ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite the importance of basal body positioning at the cell cortex, little is known about how they reach their destination ( Dawe et al, 2006 ). Centrioles have also been observed to be highly motile before cytokinesis, with a proposed function at the midbody to regulate abscission ( Piel et al, 2001 ; Krishnan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%